2008
DOI: 10.1007/s11664-008-0482-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Self-Formed Ti-Rich Interface Layers in Cu(Ti)/Low-k Samples

Abstract: In our previous studies, thin Ti-rich diffusion barrier layers were found to be formed at the interface between Cu(Ti) films and SiO 2 /Si substrates after annealing at elevated temperatures. This technique was called self-formation of the diffusion barrier, and is attractive for fabrication of ultralarge-scale integrated (ULSI) interconnects. In the present study, we investigated the applicability of this technique to Cu(Ti) alloy films which were deposited on low dielectric constant (low-k) materials (SiO x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 15 publications
2
48
0
Order By: Relevance
“…As we mentioned in the previous study, 15) the C concentration in the dielectric layers was believed to play an important role in determining compositions of the self-formed Ti-rich interface layers. Although the Si concentration in the low-k layers is similar, the C concentration of 14 at% in the low-k4 layer is lower than that in the low-k1 (17 at%).…”
Section: Resistivity Decrease As a Function Of Annealing Timementioning
confidence: 67%
See 4 more Smart Citations
“…As we mentioned in the previous study, 15) the C concentration in the dielectric layers was believed to play an important role in determining compositions of the self-formed Ti-rich interface layers. Although the Si concentration in the low-k layers is similar, the C concentration of 14 at% in the low-k4 layer is lower than that in the low-k1 (17 at%).…”
Section: Resistivity Decrease As a Function Of Annealing Timementioning
confidence: 67%
“…In the previous study, 15) Ti segregation was to occur at the Cu(Ti)/dielectric-layer interface and the Cu(Ti) surface after annealing at Ar atmosphere. In the present study, Ti segregation was observed only at the interface after annealing in UHV.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations